Two-dimensional BAs/GeC van der waals heterostructures: A widely tunable photocatalyst for water splitting and hydrogen production. (May 2023) - Islam, Md. Rasidul; Islam, Md. Sherajul; Zamil, Md. Yasir; Ferdous, Naim; Stampfl, Catherine; Park, Jeongwon; Hossain, M. Khalid
Abstract: Of late, two-dimensional van der Waals heterostructures (vdWHs) have gained tremendous attention for water-splitting to produce hydrogen (H2 ) fuel. This work demonstrates various configurations of vdWHs made up of monolayer boron arsenide (BAs) and germanium carbide (GeC) that exhibit outstanding photocatalytic properties in the water-splitting process to generate H2 fuel. The absorption coefficient of the proposed BAs/GeC vdWHs is more than 10 5 cm −1, which exceeds the extensive conversion efficiency of optoelectronic materials. The absorption coefficient can be further tuned and reaches a maximum value of 2.6 × 10 5 cm −1 when applying an external strain. Dynamically tunable bandgaps in the range of 0.78–2.02 eV are found in these vdWHs by applying a biaxial strain. A strong photocatalytic water splitting action throughout the ultraviolet to optical spectrum region is found when a biaxial strain of −6% to +6% is applied. The favorable characteristics of the proposed BAs/GeC vdWHs could help enhance H2 fuel generation via water splitting. Highlights: Model I-III of BAs/GeC vdWHs possesses a direct bandgap. A wide direct bandgap is advantageous and desired for the applications of photocatalysis. The photocatalytic water splitting of H2 production is examined by calculated the band edge position of the suggested BAs/GeC vdWHs. The biaxial strain can significantly increase their absorbance.